On the ranks of HS and McL - Ali, Faryad; Ibrahim, Mohammed Ali Faya (Utilitas Mathematica, 2006)
If G is a finite group and X a conjugacy class of G, then we define rank(G: X) to be the minimum number of elements of X generating G. In the present paper, we determine the ranks of the sporadic simple groups H S and McL. Most of the calculations were carried out using the computer algebra system GAP.